Validating Obstetric Emergency Checklists using Simulation: A Randomized Controlled Trial - Bajaj, Komal; Rivera-Chiauzzi, Enid Y.; Lee, Colleen; Shepard, Cynthia; Bernstein, Peter S.; Moore-Murray, Tanya; Smith, Heather; Nathan, Lisa; Walker, Katie; Chazotte, Cynthia; Goffman, Dena (American Journal of Perinatology, 2016)
Background The World Health Organization's Surgical Safety Checklist has demonstrated significant reduction in surgical morbidity. The American Congress of Obstetricians and Gynecologists District II Safe Motherhood Initiative (SMI) safety bundles include eclampsia and postpartum hemorrhage (PPH) checklists.Objective To determine whether use of the SMI checklists during simulated obstetric emergencies improved completion of critical actions and to elicit feedback to facilitate checklist revision.Study Design During this randomized controlled trial, teams were assigned to use a checklist during one of two emergencies: eclampsia and PPH. Raters scored teams on critical step completion. Feedback was elicited through structured debriefing.Results In total, 30 teams completed 60 scenarios. For eclampsia, trends toward higher completion were noted for blood pressure and airway management. For PPH, trends toward higher completion rates were noted for PPH stage assessment and fundal massage. Feedback resulted in substantial checklist revision. Participants were enthusiastic about using checklists in a clinical emergency.Conclusion Despite trends toward higher rates of completion of critical tasks, teams using checklists did not approach 100% task completion. Teams were interested in the application of checklists and provided feedback necessary to substantially revise the checklists. Intensive implementation planning and training in use of the revised checklists will result in improved patient outcomes.
Keywords: checklist; eclampsia; maternal hemorrhage; safety; simulation